Volume 2: Aircraft Engine; Marine; Microturbines and Small Turbomachinery 1996
DOI: 10.1115/96-gt-119
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Low-Emission Combustor for a 100-kW Automotive Ceramic Gas Turbine (III)

Abstract: A low emission combustor, which uses a prevaporization-premixing lean combustion system for the 100 kW automotive ceramic gas turbine (CGT), has been subjected to performance tests. Now a second combustor prototype (PPL-2), which incorporates improvements intended to overcome a flashback problem observed in an initial combustor prototype (PPL-1), is tested. The PPL-2 has been designed and built, so that it will substantially expand the stable combustion range. The improvement is accomplished by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The right-hand column of the table shows the measures that were incorporated in the preliminary combustor design with the aim of attaining the performance targets. The design details of typical measures were described in the previous report [2]. For instance, in order to promote better fuel atomization and mixing, a swirler and a louver were installed at the inlet to the prevaporization tube and the tube was positioned tangentially to the longitudinal axis of the lean combustion section.…”
Section: Combuster Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The right-hand column of the table shows the measures that were incorporated in the preliminary combustor design with the aim of attaining the performance targets. The design details of typical measures were described in the previous report [2]. For instance, in order to promote better fuel atomization and mixing, a swirler and a louver were installed at the inlet to the prevaporization tube and the tube was positioned tangentially to the longitudinal axis of the lean combustion section.…”
Section: Combuster Designmentioning
confidence: 99%
“…In a previous study of three types of low-NOx combustion systems, it was found that a prevaporization-premixing lean combustion system was a promising practical combustor candidate for meeting the gasoline engine passenger car emission standards [1]. This combustion system was therefore adopted to design and engineer a prototype ceramic combustor in the COT development project [2].…”
Section: Introductionmentioning
confidence: 99%